Analisis Semantik Puisi Hatiku Selembar Daun oleh Sapardi Djoko Damono - Elma Natalia Purba; Fitri Handayani Chaniago; Shafira Rahma Dina Sinaga; Asima Simbolon; Yuliana Sari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Poetry is a literary work full of meaning and symbolism. One poem that is interesting to analyze semantically is "My Heart is as Wide as a Leaf" by Sapardi Djoko Damono. In this article, we carry out an in-depth analysis of the hidden meanings in the poem. We use a semantic approach to explore the meaning of each line of poetry, identifying the metaphors, symbolism and connotations used by the poet. The analysis in this research uses a descriptive method, which describes the data naturally and produces good and coherent linguistic rules. Apart from that, we also pay attention to the structure and arrangement of words chosen by Sapardi Djoko Damono to express the implied messages in this poem. Through this analysis, we seek to understand more deeply the message the poet wants to convey, as well as explain how the use of language and symbolism in this poem can affect the reader emotionally and intellectually. It is hoped that the results of this analysis will provide new insights into Sapardi Djoko Damono's literary works and enrich understanding of modern Indonesian poetry.